The Role of Job Analysis in the Implementation of Bureaucratic Simplification in the Cimahi City Government Environment - Fahrurizki, Agung Indra; Nurasa, Heru; Halimah, Mas (Universitas Teuku Umar, 2024)
Realizing effective and efficient governance through bureaucratic simplification in all ministries, institutions, and local governments in Indonesia faces various obstacles and challenges. One of them is in the context of human resource management. This study aims to see how the Cimahi City Government implements bureaucratic simplification and runs governance with a leaner organizational structure. In this study, the researcher used a descriptive qualitative method using the concept of job structure preparation. The results of the study showed that the restructuring carried out by the Cimahi City Government was not based on an updated job analysis. So there is no definite identification related to the duties, responsibilities, and qualifications needed for each position that will have consequences for the organizational structure after the simplification of the bureaucracy. As a result, ASNs have difficulty adapting after the simplification of the bureaucracy and the emergence of redundancy in the implementation of tasks from ASNs who do not understand their new role.